Standard Laboratory-Pilot Plant Tests For Equipment Selection - D. M. Wyslouzil (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Standard testing methods are described that are presently used for the selection of grinding equipment. Correlation between laboratory batch grinding tests and pilot plant continuous tests are established by means of particle size distributions and flotation results. Conventional and autogenous grinding circuits are discussed showing the relationships of the controllable circuit parameters.